2018
DOI: 10.5964/spb.v13i1.25502
|View full text |Cite
|
Sign up to set email alerts
|

For Body and Mind: Practicing Yoga and Emotion Regulation

Abstract: The purpose of the present study was to examine if the length of yoga training may influence the use of cognitive reappraisal and expressive suppression (as emotion regulation strategies) and whether this relationship may be moderated by personality traits. Based on previous studies, we hypothesized that the link between the length of yoga practice and emotion regulation can rely most heavily on participants’ conscientiousness and extraversion levels. Ninety women in two groups participated in the study: those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 76 publications
(93 reference statements)
1
7
0
Order By: Relevance
“…The habitual use of the two emotion regulation strategies, cognitive reappraisal and expressive suppression, was measured with the Polish version of the Emotion Regulation Questionnaire (Gross and John 2003), already used in previous studies (e.g., Kobylińska et al 2018;Śmieja et al 2011). It consists of 10 questions.…”
Section: Methodsmentioning
confidence: 99%
“…The habitual use of the two emotion regulation strategies, cognitive reappraisal and expressive suppression, was measured with the Polish version of the Emotion Regulation Questionnaire (Gross and John 2003), already used in previous studies (e.g., Kobylińska et al 2018;Śmieja et al 2011). It consists of 10 questions.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, high extraversion led to increased arousal over time. There have been mixed findings regarding the moderating role of extraversion on MBM intervention outcomes [ 25 , 76 ]. Extraversion is robustly associated with positive affect; however, Smillie et al [ 77 ] showed that this positive affect could best be conceptualised as a combination of positive valence and high activation/arousal.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, high extraversion led to increased arousal over time. There have been mixed findings regarding the moderating role of extraversion on MBM intervention outcomes (Kobylińska et al, 2018;Nyklíček & Irrmischer, 2017). Extraversion is robustly associated with positive affect; however, Smillie et al (2015) showed that this positive affect could best be conceptualised as a combination of positive valence and high activation/arousal.…”
Section: Certain Personality Traits Predict Responses To Mbm Treatmentsmentioning
confidence: 99%